Effect of Import Policy on Beef Supply and Demand in Indonesia before and after the COVID-19 Pandemic - Kusumaningrum, R.; Darjanto, A.; Nurmalina, R.; Mulatsih, S.; Suprehatin (Tropical Animal Science Journal, 2024)
Beef production in Indonesia has experienced a decline after the COVID-19 pandemic, leading to an expanding gap between the supply and demand of beef. This widening gap has resulted in an increased reliance on beef imports, which in turn impacts domestic food stability. This study examines the impact of import policies on the supply and demand of beef both before and after the COVID-19 pandemic. Utilizing secondary data related to beef production, consumption, and prices, officially released by relevant ministries or institutions, the analysis was conducted using an econometric model with a simultaneous system equation. The results show that implementing a policy to decrease beef imports while concurrently increasing imports of feeder after the pandemic can enhance beef production by 25%, surpassing levels observed before the COVID-19 pandemic. Such a policy will lead to a decrease in the national beef supply, although demand will remain unchanged during both periods. By using a simultaneous equation system approach that links the dimensions of beef production and consumption, this study offers comprehensive insights for policymakers in designing policies and programs to increase Indonesia’s beef production.